2001
DOI: 10.1037/0022-3514.80.3.397
|View full text |Cite
|
Sign up to set email alerts
|

The semantic–procedural interface model of the self: The role of self-knowledge for context-dependent versus context-independent modes of thinking.

Abstract: How do independent and interdependent self-construals affect cognition? The authors proposed the semantic-procedural interface model, which distinguishes 2 such mechanisms. In addition to semantic differences, different procedural modes of thinking are associated with independent and interdependent self-construals. Independent self-definitions coincide with the tendency to process stimuli unaffected by the context in which they appear. Interdependent self-construals facilitate context-bounded thinking (i.e., p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
221
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(236 citation statements)
references
References 40 publications
11
221
2
2
Order By: Relevance
“…Following this line of reasoning, and supported with recent research by Kuhnen et al(2001) on the semantic-procedural interface model of the self, we postulated that there may be differences in information processing style associated with connectedness, egoistic, and biospheric concerns. We predicted that less connection with nature would be associated with more local information processing, while a greater connection would be associated with global processing.…”
Section: Stated In His Green History Of the Worldsupporting
confidence: 76%
See 1 more Smart Citation
“…Following this line of reasoning, and supported with recent research by Kuhnen et al(2001) on the semantic-procedural interface model of the self, we postulated that there may be differences in information processing style associated with connectedness, egoistic, and biospheric concerns. We predicted that less connection with nature would be associated with more local information processing, while a greater connection would be associated with global processing.…”
Section: Stated In His Green History Of the Worldsupporting
confidence: 76%
“…In some cultures, self is defined broadly and interconnected with other people, while in other cultures self is defined more narrowly and independent of other people (cf. Markus & Kitayama, 1991;Singelis, 1994;Kuhnen et al, 2001). Perhaps, a connection with nature is simply an extension of an interdependent self; not only is who I am dependent on my relationship with other people, but who I am is also dependent on my relationship with the environment around me.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…For example, Kühnen and colleagues (11,12) found that Western participants exhibited more holistic attention when they were encouraged to think about the ways in which they are similar to family members and friends or when they were asked to circle first-person plural pronouns (we, us, ours, etc.) in a paragraph.…”
mentioning
confidence: 99%
“…Self-direction values entail a creative, exploratory mind-set that is less concerned about prevailing social standards. Creativity itself entails following novel directions without rigid application of fixed rules and norms (Kuhnen, Hannover, & Schubert, 2001). Thus, although this pursuit can entail cleanliness (as in five-star restaurants and some art studios), it involves a mind-set that can often be inimical to this behavior.…”
Section: Methodsmentioning
confidence: 99%